TRANSACTION ORDERING VIA LAMPORT LOGICAL TIMESTAMPS TO MITIGATE MEV EXTRACTION IN ETHEREUM SMART CONTRACTS - CHERKAS, NAZARII; BATYUK, ANATOLIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The increasing prevalence of Maximal Extractable Value (MEV) in blockchain networks has highlighted critical challenges in achieving fair and predictable transaction ordering. On Ethereum, where block builders possess unrestricted control over transaction sequencing, users face significant risks from frontrunning and sandwich attacks, particularly within decentralized finance (DeFi) applications interacting with shared contract states. To address this issue, this paper proposes a hybrid MEV mitigation method employing Lamport-style logical clocks, designed to establish a local causal ordering mechanism within individual smart contracts.The proposed approach equips each smart contract, such as a decentralized exchange liquidity pool, with a local logical timestamp counter. Transactions submitted to the contract carry logical timestamps, enabling the enforcement of a causally consistent execution order. A key benefit of this method is that it does not necessitate alterations to Ethereum’s global consensus mechanism, thus ensuring compatibility with the current Ethereum ecosystem, as well as rollups and modular app-chain architectures. The study details the protocol design, explores various implementation strategies for both on-chain and off-chain execution environments, and addresses resilience against adversarial attempts such as timestamp manipulation and denial-of-service attacks.The primary advantage of this approach lies in its effectiveness in mitigating intra-contract MEV extraction by strictly controlling transaction reordering for conflicting state interactions, while preserving concurrency for non-conflicting transactions. Findings indicate that the use of local Lamport clocks provides a practical, low-overhead solution for MEV-sensitive applications, including decentralized exchanges and rollup sequencing systems.
Keywords: blockchain; smart contracts; distributed systems; peer-to-peer networks; cryptography